Effect of Air Tamponade among Patients with Epiretinal Membranes and Intraretinal Cystoid Changes Undergoing Vitrectomy with Membrane Peeling – A Prospective Randomized Trial - Leisser, Christoph; Ruiss, Manuel; Pilwachs, Caroline; Hienert, Julius; Stjepanek, Kristina; Findl, Oliver (Klinische Monatsblätter für Augenheilkunde, 2021)
Background The effect of air tamponade among patients undergoing vitrectomy with membrane peeling for removal of epiretinal membranes (ERM) is controversially discussed. The aim of the present study was to analyze differences in outcomes between air tamponade and balanced salt solution (BSS) in a study population with preoperative intraretinal cystoid changes.Patients and Methods This randomized study included patients scheduled for pars plana vitrectomy with membrane peeling owing to ERM and intraretinal cystoid changes. Air tamponade or BSS at the end of surgery was applied according to preoperative randomization. Optical coherence tomography and best-corrected distance visual acuity (DCVA) measurements were performed before surgery, 5 days after surgery, and 3 months after surgery.Results From 96 patients included, 85 eyes had full follow-up and could be included for analysis. Median improvement of DCVA was + 16 EDTRS letters (IQR: 8 to 22) among patients with BSS, while it was + 13 EDTRS letters (IQR: 8 to 17) among patients with air tamponade. There was a trend for better improvement of DCVA when BSS was left at the end of surgery, compared to air tamponade, but not reaching statistical significance.Conclusions There were no statistically significant differences concerning resorption of preoperative intraretinal cystoid changes, improvement of visual acuity, and final DVCA between air tamponade and BSS.Hintergrund Die Auswirkungen der Lufttamponade bei Patienten nach Vitrektomie mit Membrane Peeling aufgrund von epiretinalen Membranen (ERM) werden kontrovers diskutiert. Ziel der Studie ist es, Unterschiede in den Ergebnissen zwischen Lufttamponade und „balanced salt solution“ (BSS) in einer Patientengruppe mit präoperativen intraretinalen zystoiden Veränderungen zu untersuchen.Patienten und Methoden Diese randomisierte prospektive Studie inkludierte Patienten mit ERM und intraretinalen zystoiden Veränderungen, die zur Pars-plana-Vitrektomie mit Membrane Peeling vorgesehen waren. Lufttamponade oder BSS am Ende der Operation wurde entsprechend der Randomisierung durchgeführt. Optische Kohärenztomografie und Bestimmung des bestkorrigierten Fernvisus (DCVA) erfolgten präoperativ, 5 Tage und 3 Monate nach der Operation.Resultate Von 96 in die Studie rekrutierten Patienten hatten 85 ein vollständiges „follow-up“ und konnten in die Analysen der Ergebnisse eingeschlossen werden. Die mediane Verbesserung des DCVA war + 16 ETDRS-Buchstaben (IQR: 8 – 22) bei Patienten mit BSS und + 13 ETDRS-Buchstaben (IQR: 8 – 17) bei Patienten mit Lufttamponade. Es zeigte sich ein Trend für eine stärkere Verbesserung des DCVA bei BSS verglichen zur Lufttamponade, jedoch nicht statistisch signifikant.Schlussfolgerung Es zeigten sich keine statistisch signifikanten Unterschiede in Bezug auf Resorption der präoperativen intraretinalen zystoiden Veränderungen, Verbesserung des DCVA und des postoperativen DCVA zwischen BSS und Lufttamponade.
Keywords: air tamponade; epiretinal membranes; vitrectomy with membrane peeling; intraretinal cystoid changes